Metabolic fluxes for nutritional flexibility of Mycobacterium tuberculosis. Issue 5 (4th May 2021) - Borah, Khushboo; Mendum, Tom A; Hawkins, Nathaniel D; Ward, Jane L; Beale, Michael H; Larrouy‐Maumus, Gerald; Bhatt, Apoorva; Moulin, Martine; Haertlein, Michael; Strohmeier, Gernot; Pichler, Harald; Forsyth, V Trevor; et al.
Abstract: The co‐catabolism of multiple host‐derived carbon substrates is required by Mycobacterium tuberculosis (Mtb) to successfully sustain a tuberculosis infection. However, the metabolic plasticity of this pathogen and the complexity of the metabolic networks present a major obstacle in identifying those nodes most amenable to therapeutic interventions. It is therefore critical that we define the metabolic phenotypes of Mtb in different conditions. We applied metabolic flux analysis using stable isotopes and lipid fingerprinting to investigate the metabolic network of Mtb growing slowly in our steady‐state chemostat system. We demonstrate that Mtb efficiently co‐metabolises either cholesterol or glycerol, in combination with two‐carbon generating substrates without any compartmentalisation of metabolism. We discovered that partitioning of flux between the TCA cycle and the glyoxylate shunt combined with a reversible methyl citrate cycle is the critical metabolic nodes which underlie the nutritional flexibility of Mtb. These findings provide novel insights into the metabolic architecture that affords adaptability of bacteria to divergent carbon substrates and expand our fundamental knowledge about the methyl citrate cycle and the glyoxylate shunt. Synopsis: Quantitative metabolic analysis using stable isotopes, lipid fingerprinting, and mathematical modelling are applied to investigate the metabolic network of Mycobacterium tuberculosis growing slowly in a steady state chemostat system. The tubercle bacillus efficiently co‐metabolises cholesterol or glycerol, in combination with two‐carbon generating substrates without compartmentalisation of metabolism. Metabolic flux profiles of M . tuberculosis growing slowly on the dual carbon sources are described using an expanded 13C isotopomer model. Partitioning of metabolite flux between the TCA cycle and the glyoxylate shunt combined with a reversible methyl citrate cycle are critical nodes underlying the metabolic flexibility of M. tuberculosis . Abstract : Quantitative metabolic analysis using stable isotopes, lipid fingerprinting, and mathematical modelling are applied to investigate the metabolic network of Mycobacterium tuberculosis growing slowly in a steady state chemostat system.